Rage : on being queer, black, brilliant... and completely over it - Fabian Brathwaite, Lester (Tiny Reparations Books, 2024)
"A debut book from Entertainment Weekly writer and former Out magazine editor Lester Fabian Brathwaite, Rage is a darkly comedic exploration of Blackness, queerness, and the American Dream, at a time when creative anger feels like the best response to inequality"--